Marketing the academic library on the web - Kaur, K. (2009)
Purpose - The purpose of this paper is to describe the marketing initiatives taken by academic libraries to promote collection and services to their clientele. It specifically aims to examine academic library web sites for marketing approach, promotional and public relations activities. Design/methodology/approach - The study relies heavily on web site exploration and interviews with library managers. A total of 22 library web sites were examined based on pre-determined criteria developed from the extant literature and initial web site investigation. The paper also draws upon the authors' personal experiences and observations. Interviews were used to investigate university library manager's level of awareness of the library web site as a marketing tool and how they perceived this to be used to the library's advantage. Findings - It is found that academic libraries are lacking in their promotional activities. Library web sites are not fully utilized as a marketing tool and an enabler to reach out to the community for promotion of services and collections. Research limitations/implications - The study is limited to Malaysian university libraries, therefore generalization to others is to be cautioned but there are important lessons to be learnt. Practical implications - This paper will be helpful to libraries planning to implement a marketing strategic plan to improve its outreach to users and enhance the users' image of the library. Originality/value - A study such as this is new in Malaysia and reveals several marketing strategies that may be useful to other academic libraries.